AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN ALPUKAT (Persea americana Mill.) TERHADAP BAKTERI Staphylococcus epidermidis - Fara Azzahra; Vyanka Madhani (Jurnal Insan Farmasi Indonesia, 2021)
Avocado leaves has known to have antibacterial activity. This study aim to determine the antibacterial activity of avocado leaf juice and ethanol extract against S. epidermidis bacteria. Antibacterial activity tests were carried out using juice and ethanol extract of avocado leaves at concentrations of 2%, 4%, 6%, 8%, 10%, positive control ciprofloxacin 5µg/disk, sterile distilled water negative control, 96% ethanol solvent control. The data obtained were statistically analyzed using Mann Whitney. The inhibition zones formed were categorized according to the Clinical and Laboratory Standards Institute. Avocado leaf ethanol extract had antibacterial activity against S. epidermidis bacteria at concentrations of 2%, 4%, 6%, 8% and 10% of 7.68±0.16mm; 7.54±0.02 mm; 7.89±0.21mm; 8.18±0.04 mm and 8.50±0.28 mm with the category of resistance. The diameter of the ciprofloxacin inhibition zone was 35.98±0.03mm with a sensitive category. Statistically, avocado leaf ethanol extract had a significant difference to ciprofloxacin, avocado leaf juice had no antibacterial effect at all concentrations. The conclusion of the study, avocado leaf juice did not have antibacterial activity, while the ethanol extract of avocado leaves had antibacterial activity against S. epidermidis bacteria, but its potency was not comparable to ciprofloxacin in inhibiting the growth of S. epidermidis bacteria.